Design and Evaluation of Gastro retentive Drug Delivery System of Anti Ulcer Drug - Patil, J S (Fakultas Farmasi, Universitas Gadjah Mada, 2015)
Floating matrix tablets of Lansoprezol were developed to prolong gastric residence time, leading to sustained action of the drug. Tablets were prepared by wet granulation technique, using hydroxypropylmethyl-cellulose as a polymer in two different grades, HPMC K4M and HPMC K15M. Tablets were evaluated for their physical characteristics, viz., hardness, thickness, friability, mass variation, drug content and floating properties. Further, tablets were studied for in vitro drug release characteristics for 24 hours. The tablets exhibited controlled and prolonged drug release profiles while floating over the dissolution medium. Non-Fickian diffusion was confirmed as the drug release mechanism from these tablets, indicating that water diffusion and polymer rearrangement played an essential role in drug release. The best formulation (F4) was selected based on in vitro characteristics and was used in vivo radiography studies by incorporating barium sulphate. These studies revealed that the tablets remained in the stomach for 12 hours in fasting rabbits and indicated that gastric retention time was increased by the floating principle, which was considered desirable for the absorption window drugs.Keywords: Lansoprezol; floating tablets; gastric residence time; gastroretentive drug delivery system